Effect of different finishing times on surface roughness and maintenance of polish in nanoparticle and microhybrid composite resins. - da Silva, João Maurício Ferraz [UNESP]; da Rocha, Daniel Maranha; Travassos, Alessandro Caldas; Fernandes Jr., Virgílo Vilas Boas; Rodrigues, José Roberto (My University, 2010)
The objective of the study was to evaluate the effect of immediate polishing, after 24 h and after 1 week, on the surface roughness of two micro-hybrid resins (Esthet-X; Opallis) and one nanoparticle resin (Filtek Z350), as well as verifying maintenance of the polish after 1 year, simulated by means of thermal cycling. Forty-three specimens of each material were made and divided into a control group and three experimental groups. The control group specimens received no surface treatment. Group 1 received finishing with an extra-fine diamond drill and posterior polishing with the systems Enhance and PoGo, immediately after polymerization. Group 2 received the same procedures; however, these were carried out after 24 h of storage. Group 3 received the surface treatment after 7 days of storage. After that, the surface roughness was evaluated by a profilometer. After the initial reading, the specimens were submitted to thermal cycling for 10,000 cycles. After thermal cycling, a new roughness reading was taken. The results showed a higher roughness value for the resin Esthet-X, and the resins Opallis and Z350 presented the same roughness values. As regards the time when polishing was performed, specimens polished immediately after polymerization presented higher roughness values in comparison with the other two periods. After thermal cycling, the statistical analysis showed that the Opallis resin polish had been maintained, whereas for the other two resins, there was a significant reduction in surface smoothness. The surface roughness was influenced by the material and also by the period of polishing; the surface roughness of all tested materials were at a clinically acceptable level.